Meta-analysis of the acute effects of anodal transcranial direct current stimulation on athletic performance - Jiang, M.; Liu, Y.; Gao, X. (Frontiers in Physiology, 2025)
Objective: Systematically evaluate the acute effects of anodal transcranial direct current stimulation (a-tDCS) on athletes` sport-specific performance and identify the optimal stimulation parameters and target brain regions for enhancing sport-specific performance.